Spectroscopic Studies on the Interaction of Polydatin with Bovine Serum Albumin - Liu, Xiaoli; Li, Hua (Asian Journal of Chemistry, 2013)
The interaction of polydatin with bovine serum albumin has been studied by spectroscopic methods including fluorescence, ultraviolet-visible and Fourier transform infrared spectroscopy. The intrinsic fluorescence of bovine serum albumin is quenched in the presence of polydatin and the quenching mechanism is suggested as static quenching procedure. The thermodynamic parameters DH and DS are estimated to be -49.92 kJ mol-1 and -78.81 J mol-1 K-1, which indicates that the interaction of polydatin with bovine serum albumin is driven mainly by hydrogen bonds and van der Waals interactions. The number of binding sites of polydatin to bovine serum albumin is approximately equal to unity and the competitive experiments suggest that the binding site is probably located on site II of bovine serum albumin. The quantitative analysis of infrared spectra data shows that the binding stabilizes the a-helix and b-sheet structure of bovine serum albumin at the cost of a loss in the b-turn structure.